Vagotomy and Gastric Tumorigenesis - Rabben, Hanne-Line; Zhao, Chun-Mei; Hayakawa, Yoku; C. Wang, Timothy; Chen, Duan (Current Neuropharmacology, 2016)
Vagotomy reduces gastric acid secretion and was therefore introduced as a surgical treatment for peptic ulcers in the 1970s. Later, it was replaced by acid reducing medication, such as histamine type 2 (H2) receptor antagonists and proton pump inhibitors (PPIs). A large body of evidence has indicated that drug-induced hypochlorhydria per se does not increase the risk of gastric cancer. Early studies on the effects of vagotomy in chemically-induced rodent models of gastric cancer reported an increased risk of developing gastric cancer. This was most likely due to a delayed gastric emptying, which later has been accounted for by including an additional drainage procedure, e.g. pyloroplasty. In a recent study using three different mouse models of gastric cancer (including genetically engineered, chemically-induced and Helicobacter pylori-infected mice), either unilateral vagotomy or bilateral truncal vagotomy with pyloroplasty was found to significantly attenuate tumorigenesis in the denervated side of the stomach at early preneoplastic stages as well as at later stages of tumorigenesis. Consistently, pharmacological denervation using botulinum toxin A or muscarinic acetylcholine receptor 3 (M3R) blockade inhibited tumorigenesis. Moreover, it was found that recurrence of gastric cancer was reduced in patients following vagotomy. Thus, these new findings suggest the potential treatment strategies to target the nerve, neurotransmitters, corresponding receptors and their downstream signaling pathways for the malignancy.
Keywords: stem cell signaling